Pengaruh Lingkungan Sekolah Dan Pemebelajaran Pendidikan Agama Islam Terhadap Pembentukan Karakter Siswa SMA Negeri Di Kota Bontang - Permana, Kiki; Zurqoni, Zurqoni; Kusasi, M (el Buhuth: Borneo Journal of Islamic Studies, 2020)
This research is motivated by several factors that can affect the character of students, including the school environment, and the learning of Islamic Religious Education. Where the character of school students at this time experiencing deterioration with the occurrence of delinquency-delinquency, crime, violence and disorder in the community. Through the school environment and learning Islamic Religious Education can affect the formation of character in students. The purpose of the study was whether there is an influence of the school environment on the character of students, whether there is an influence of Islamic Religious Education Learning on the character of students, and whether there is simultaneously the influence of the school environment, and Islamic Religious Education Learning on the formation of the character of students in Bontang State High School. This type of research is a quantitative research with data collection techniques in the form of observation, questionnaires, and interviews. Data analysis techniques used are multiple linear regression analysis and hypothesis testing (T test and F test). The population is all 11th grade students of SMA Negeri Bontang totaling 694 students. Sampling technique with purposive sampling of 87 students. The results showed positive based on the positive questions asked makes children positive that there is an influence of the school environment on the formation of student character with a regression coefficient value of 0.611 with T table 1.989 < 3.780 t calculate so that Ha is accepted, there is an influence of Islamic Education Learning on the formation of student character with a regression coefficient value of 0.564 with T table 1.989 < 3.824 t calculate so that Ha is accepted, simultaneously there is the influence of the school environment and learning of Islamic Religious Education on the formation of student character by 0.686 with the value of F Table 3.105 < 37.380 F count so that Ha is accepted.